Abortion in Chile (1874-2023): Constitutional and criminal law perspectives (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
In Chile, according to Law 21.030/2017, interruption of pregnancy is allowed on the following grounds: 1) there is a risk to the life of the pregnant woman; 2) the fetus is unviable; 3) the pregnancy resulted from rape. The current justification of abortion – otherwise sanctioned by the Chilean Penal Code of 1874 – goes beyond the regime previously imposed by the Health Code, which, while allowing therapeutic abortion from 1931, starting from 1989 forbade any action whose purpose was to cause a pregnancy interruption. During the legislative process, the Constitutional Court recognized that the fundamental rights of the woman (as a person) take precedence over the protection granted to the unborn child by the Chilean Constitution of 1980.
Keywords: Chile; therapeutic abortion; voluntary termination of pregnancy; protection of nasciturus; conscientious objection